Pengembangan Desa Wisata Kreatif Kampung Jamu Di Desa Nguter, Sukoharjo Pendekatan Pada Arsitektur Ramah Lingkungan - Mu'arif Darojatun, Mu'arif, Ir. Alpha Febela Priyatmono, MT, Rini Hidayati, ST. MT (2016)
Jamu is genuine ingredients Indonesia, which uses to maintain health, prevent disease, treat illness, disease, and to restore the beauty products. The exsitence of tradisional herbal medicine in Indonesia is not strange anymore for the community,because since ancient times our ancestors were already consumsing tradisional herbal medicine to maintain health or treat disease. With the awareness back to nature, the use of tradisional herbal medicine made from natural raw materials without any elemnt of this chemical should be considered for a health problem than drugs that smelled of chemicals. Nguter village as the locatian of the home industry is essentially aimed at improving the quality of Nguter village area to be exploited and explore the potensial that exists as a tourist area of tradisional herbal medicine industry, to achieve the optimal conditions of all that is therein. Keywords : Back To Nature